Analyzing the Application of the Business Judgment Rule under Law No. 16 of 2025 and Supreme Court Circular Letter No. 4 of 2016: Analisis Penerapan Business Judgment Rule Berdasarkan UU No. 16 Tahun 2025 dan SEMA No. 4 Tahun 2016 - Anita Audina; Melinda Melinda; Marjan Marjan; Muhammad Nurcholis Alhadi (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study examines the shift in the legal paradigm regarding the legal status and criminal liability for the management of State-Owned Enterprises (SOEs) following the enactment of Law No. 1 of 2025 on SOEs, as well as its relevance to Supreme Court Circular Letter (SEMA) No. 4 of 2016 in Case No. 10/Pid.Sus -TPK/2025/Pn.Smr. The background of this study is the existence of overlapping regulations: new provisions assert that the directors, commissioners, and supervisory board members of SOEs are no longer considered state officials, while current practices still rely on old guidelines when assessing state losses. This study is a normative legal study employing a legislative and conceptual approach, utilizing descriptive-qualitative analysis of primary and secondary legal sources. The results of this study indicate that the 2025 SOE Law reinforces the separation of state assets—which have been distinct from the corporate assets of an SOE—thereby classifying risks that should be treated as business risks protected by the business judgment rule, provided they are undertaken in good faith, with due diligence, and without a conflict of interest. However, SEMA No. 4 of 2016 still allows judges the discretion to assess and determine the existence of state losses in specific cases, thereby creating the potential for overlap between the two existing regulations and the risk of over-criminalization of SOE business decisions. The conclusion of this study is that the author.